The association of mental disorders with perceived social support, and the role of marital status: results from a national cross-sectional survey - Janhavi Ajit Vaingankar; Edimansyah Abdin; Siow Ann Chong; Saleha Shafie; Rajeswari Sambasivam; Yun Jue Zhang; Sherilyn Chang; Boon Yiang Chua; Shazana Shahwan; Anitha Jeyagurunathan; Kian Woon Kwok; Mythily Subramaniam (BMC, 2020)
Abstract Background This study investigated whether (i) mental disorders were associated with perceived social support and its subcomponents, (ii) current marital status was related to perceived social support, and (iii) 'Married' status influenced the relationship between mental state and perceived social support. Methods Data from a cross-sectional national survey comprising 6126 respondents were used. Lifetime diagnosis for five mental disorders was assessed with a structured questionnaire. Perceived social support was measured with the Multidimensional Scale of Perceived Social Support (MSPSS) that provides Global and subscale scores for Significant Other, Family and Friends. Multiple linear regression analyses were conducted to address the research questions with MSPSS score as the dependent variable. Structural equation modeling (SEM) was performed to test mediation by marital status. Results All mental disorders included in the study, except alcohol use disorder (AUD), were significantly and negatively associated with Global MSPSS scores. After controlling for sociodemographic factors and chronic physical illness, major depressive disorder (β = - 0.299, 95% CI: -0.484 - -0.113, p = 002) and having any of the five mental disorders (β = - 0.133, 95% CI: -0.254 - -0.012, p = 032) were negatively associated with support from Significant Other, while support from Family and Friends was lower among all disorders, except AUD. Being married was positively associated with perceived social support in people with and without mental disorders. Results of the SEM partially support mediation by mental state - perceived social support relationship by 'Married' status. Conclusion Having mental disorders was associated with lower perceived social support. Being married has potential to influence this relationship.